Basal Cell Adenoma – A Report of a Rarity in a Relatively Rare Site - Kavitha.M; Niveditha.B; Mutum Sangeeta Devi; Manju.J; Vishnu Priya.CK (Institute of Medico-legal Publications Pvt Ltd, 2021)
Basal cell adenoma is a rare benign neoplasm of the salivary gland. It preferentially occurs in the parotid glandand upper lip during the sixth and seventh decades of life. The clinical presentation most frequently seenis a slow-growing, asymptomatic, movable, round or oval, normally coloured submucosal mass measuringless than 3.0 cm in diameter, encapsulated and well circumscribed. Histologically, the tumor consists of aproliferation of the terminal duct epithelial cells forming islands and sheets with sparse of fibrous stroma,and numbers of small myoepithelial cells are present . Here is a report of a rare case of basal cell adenomain a relatively rare site of palate presented to our department.